THU0172 Sleep quality in elderly patients with rheumatoid arthritis should be kept in mind. (12th June 2018) - Deniz, O.; Satis, H.; Cavusoglu, C.; Salman, R.B.; Varan, O.; Atas, N.; Coteli, S.; Dogrul, R.T.; Babaoglu, H.; Oncul, A.; Varan, H.D.; Kizilarslanoglu, M.C.; et al.
Abstract : Background: Sleep disturbance is one of the most important geriatric syndromes and its evaluation is part of the routine comprehensive geriatric assessment (CGA). Elderly patients with poor sleep quality are at risk of worse clinical outcomes such as falling, impairment of activities of daily living, depression and anxiety. Rheumatoid arthritis (RA) is an inflammatory disorder characterised by joint pain and may worsen sleep quality. Previous clinical trials in the literature have shown that elderly patients with RA have poorer sleep quality compared to younger patients. However, there is lack of data on sleep quality of elderly patients with RA. Objectives: We aimed to investigate sleep quality of elderly patients with and without RA and also explore the effects of sleep quality on quality of life (QoL) and its association with disease activity. Methods: This study was conducted in the Geriatric and Rheumatology outpatient clinics at a tertiary University Hospital. Fifty elderly RA patients diagnosed according to the ACR criteria and 30 age-matched controls without inflammatory arthritis were included in the study. All patients underwent CGA including evaluation of Basic Activities of Daily Living (ADL), Instrumental ADL, Yesavage Depression Scale (YDS), Mini-Mental State Examination, handgrip strength and Mini-Nutritional Assessment-Short Form. Sleep quality was assessed by Pittsburg Sleep Quality Index (PSQI), disease activity with Disease Activity Score 28 (DAS28-CRP) and QoL with RA QoL questionnaire (RAQoL). Results: The median age was 70 years (min-max: 65–86) and 62.5% was female. Age, gender and co-morbidities, such as hypertension, coronary artery disease, osteoporosis, urinary incontinence, depression and chronic obstructive pulmonary disease, and comprehensive geriatric assessment parameters were similar between two groups. Diabetes mellitus frequency was higher in the control group compared to RA patients (43.3% vs. 22.0%, p=0.044). Median PSQI global score was higher in elderly patients with RA compared to controls [9 (min-max: 1–20) vs. 5 (min-max: 1–13), p=0.029), indicating poorer sleep quality. In elderly patients with RA, DAS28-CRP score significantly correlated with PSQI global (r=0.514, p<0.001) and RAQoL scores (r=0.493, p<0.001). PSQI global score also significantly correlated with RAQoL score (r=0.689, p<0.001), number of medication (r=0.324 p=0.022), handgrip strength (r=−0.370, p=0.017) and YDS score (r=0.417, p=0.005). Conclusions: Our results suggest that elderly patients with RA may have poorer sleep quality compared to elderly control patients. Disease activity of RA had adverse effects on both sleep quality and QoL. In daily practice, when evaluating an elderly RA patient, sleep quality should also be assessed. Further studies are needed to investigate if management of sleep disturbances improve quality of life in elderly patients with RA. Disclosure of Interest: None declared